Experimental benchmark control problem for multi-axial real-time hybrid simulation - Condori Uribe, Johnny W.; Salmeron, Manuel; Patino, Edwin; Montoya, Herta; Dyke, Shirley J.; Silva, Christian E.; Maghareh, Amin; Najarian, Mehdi; Montoya, Arturo (Frontiers in Built Environment, 2023)
Advancing RTHS methods to readily handle multi-dimensional problems has great potential for enabling more advanced testing and synergistically using existing laboratory facilities that have the capacity for such experimentation. However, the high internal coupling between hydraulics actuators and the nonlinear kinematics escalates the complexity of actuator control and boundary condition tracking. To enable researchers in the RTHS community to develop and compare advanced control algorithms, this paper proposes a benchmark control problem for a multi-axial real-time hybrid simulation (maRTHS) and presents its definition and implementation on a steel frame excited by seismic loads at the base. The benchmark problem enables the development and validation of control techniques for tracking both translation and rotation degrees of freedom of a plant that consists of a steel frame, two hydraulic actuators, and a steel coupler with high stiffness that couples the axial displacements of the hydraulic actuators resulting in the required motion of the frame node. In this investigation, the different components of this benchmark were developed, tested, and a set of maRTHS were conducted to demonstrate its feasibility in order to provide a realistic virtual platform. To offer flexibility in the control design process, experimental data for identification purposes, finite element models for the reference structure, numerical, and physical substructure, and plant models with model uncertainties are provided. Also, a sample example of an RTHS design based on a linear quadratic Gaussian controller is included as part of a computational code package, which facilitates the exploration of the tradeoff between robustness and performance of tracking control designs. The goals of this benchmark are to: extend existing control or develop new control techniques; provide a computational tool for investigation of the challenging aspects of maRTHS; encourage a transition to multiple actuator RTHS scenarios; and make available a challenging problem for new researchers to investigate maRTHS approaches. We believe that this benchmark problem will encourage the advancing of the next generation of controllers for more realistic RTHS methods.